Turkish Foreign Policy under AKP Rule: Making Sense of the Turbulence - Cop, Mehmet Burak; Zihnioğlu, Özge (Sage Publications Ltd, 1 Olivers Yard, 55 City Road, London EC1Y 1Sp, England, 2017)
The twists and turns of Turkish foreign policy under Justice and Development Party (AKP) rule have been a matter of interest not only in the scholarly literature, but also in common discourse. This article traces the unfolding of this policy in Turkey's neighbourhood and in relation to its quest for EU membership, particularly since 2006, and also discusses the milestones that have been shaping it. Drawing upon the categories of change Charles Hermann identified, this article illustrates the magnitude and direction of change in Turkish foreign policy during this period and critically evaluates its implications for this policy today.
Keywords: Turkish foreign policy; foreign policy change; Ahmet Davutoglu; Justice and Development Party (AKP); Middle-East; Turkey